Coronary artery bypass grafting following stent restenosis - Sun, Zhonghua (2016)
Coronary artery bypass grafting (CABG) is the gold standard for treatment of patients with coronary artery disease. In recent years, a less invasive technique, percutaneous coronary intervention (PCI), has been increasingly used in clinical practice due to technical improvements, in particular the widespread use of drug-eluting stents (DES). However, clinical outcomes of these two approaches in treating coronary artery disease remain to be determined. This chapter provides an overview of the clinical benefi ts of CABG over PCI using coronary stenting. Hybrid approaches of combining CABG with PCI, and CABG following coronary stent restenosis are discussed, while computational hemodynamic modeling of CABG treatment strategy is highlighted.